Comparison between wound healing in induced diabetic and nondiabetic rats after low-level laser therapy - Rabelo, Sylvia Bicalho; Villaverde, Antonio Balbin; Nicolau, Renata Amadei; Salgado, Miguel A. Castillo; Melo, Milene da Silva; Pacheco, Marcos Tadeu T. (Mary Ann Liebert, Inc., 2006)
Objective: the aim of this work was to compare the effect of low-level laser therapy (LLLT) on the wound healing process in nondiabetic and diabetic rats. Background Data: Among the clinical symptoms caused by diabetes mellitus, a delay in wound healing is a potential risk for patients. It is suggested that LLLT can improve wound healing. Methods: the tissue used for this study was extracted from animals suffering from diabetes, which was induced by Streptozotocin (R), and from nondiabetic rats. Animals were assembled into two groups of 25 rats each (treated and control) and further subdivided into two groups: diabetic (n = 15) and nondiabetic (n = 10). A full-thickness skin wound was made on the dorsum. area, with a round 8-mm hole-punch. The treated group was irradiated by a HeNe laser at 632.8 nm, with the following parameters: 15 mW, exposition time of 17 sec, 0.025 cm(2) irradiated area, and energy density of 10 J/cm(2). Square full-thickness skin samples (18 mm each side, including both injured and noninjured tissues) were obtained at 4, 7, and 15 days after surgery and analyzed by qualitative and quantitative histological methods. Results: Quantitative histopathological analysis confirmed the results of the qualitative analysis through histological microscope slides. When comparing tissue components (inflammatory cells, vessels and fibroblast/area), we found that treated animals had a less intense inflammatory process than controls. Conclusion: Results obtained by both qualitative and quantitative analyses suggested that irradiation of rats with HeNe (632.8 nm), at the tested dose, promoted efficient wound healing in both nondiabetic and diabetic rats as, compared to the control group.